A short walk through a wide world eaudiobook A novel. - Westerbeke, Douglas (Simon & Schuster Audio, 2024)
"Imagine The Life of Pi, The Alchemist , and The Midnight Library rolled into one fantastical fable." — The New York Times Book Review * "An epic adventure...rich with all the possibilities the world can hold." — People NATIONAL BESTSELLER • A dazzlingly epic debut that charts the incredible, adventurous life of one woman as she journeys the globe trying to outrun a mysterious curse that will destroy her if she stops moving. Paris, 1885: Aubry Tourvel, a spoiled and stubborn nine-year-old girl, comes across a wooden puzzle ball on her walk home from school. She tosses it over the fence, only to find it in her backpack that evening. Days later, at the family dinner table, she starts to bleed to death. When medical treatment only makes her worse, she flees to the outskirts of the city, where she realizes that it is this very act of movement that keeps her alive. So begins her lifelong journey on the run from her condition, which won't allow her to stay anywhere for longer than a few days—nor return to a place where she's already been. From the scorched dunes of the Calanshio Sand Sea to the snow-packed peaks of the Himalayas; from a bottomless well in a Parisian courtyard, to the shelves of an infinite underground library, we follow Aubry as she learns what it takes to survive and ultimately, to truly live. But the longer Aubry wanders and the more desperate she is to share her life with others, the clearer it becomes that the world she travels through may not be quite the same as everyone else's... Fiercely independent and hopeful, yet full of longing, Aubry Tourvel is an unforgettable character fighting her way through a world of wonders to find a place she can call home. A spellbinding and inspiring story about discovering meaning in a life that seems otherwise impossible, A Short Walk Through a Wide World reminds us that it's not the destination, but rather the journey—no matter how long it lasts—that makes us who we are.